2000
DOI: 10.1136/gut.46.4.460
|View full text |Cite
|
Sign up to set email alerts
|

Atrophic gastritis and Helicobacter pylori infection in outpatients referred for gastroscopy

Abstract: Background-Atrophic gastritis has been shown to be one of the long term sequelae of Helicobacter pylori infection. Aims-To determine the prevalence of atrophic gastritis in outpatients, to study the accuracy of serological methods for revealing atrophy, and to define the association of H pylori infection with atrophic gastritis in these patients. Patients/methods-A total of 207 consecutive outpatients referred for gastroscopy were included. Biopsy specimens from the antrum and corpus were assessed histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 22 publications
8
55
2
1
Order By: Relevance
“…It has been reported in sev- [4,23] . In the present study, infection with H pylori CagA + is associated with atrophic gastritis of the antrum, but not of the body, results which are in accordance with those reported by Oksanen et al, 2000 [24] . Indeed, in a stomach affected by ABG, the microenvironment is more hostile for the survival and growth of H pylori promoting spontaneous eradication of the bacteria and a progressive decline in concentrations of serum antibodies to H pylori [25][26][27] .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has been reported in sev- [4,23] . In the present study, infection with H pylori CagA + is associated with atrophic gastritis of the antrum, but not of the body, results which are in accordance with those reported by Oksanen et al, 2000 [24] . Indeed, in a stomach affected by ABG, the microenvironment is more hostile for the survival and growth of H pylori promoting spontaneous eradication of the bacteria and a progressive decline in concentrations of serum antibodies to H pylori [25][26][27] .…”
Section: Discussionsupporting
confidence: 82%
“…H pylori and its virulence factor CagA may be involved in processes during the early stages of inflammation of the antrum that lead to extension of atrophic gastritis towards the gastric body [29] . In concordance with other studies, infection with H pylori-CagA + is associated with low PGI/PGII ratios [24] . Several studies have reported an association of low PGI concentrations and low PGI/PGII ratios with precancerous lesions as well as with gastric cancer [30][31][32] .…”
Section: Discussionsupporting
confidence: 78%
“…Bunun da glukoz metabolizmasındaki değişikliklerin HP kolonizasyonunun hazırlanmasında bir rolü olduğuna bağlamışlardır. Diyabet ve obesite sırasında gözlenen azalmış gastrik motilite (59,60) ve musinlerin nonenzimatik reaksiyonu ile gastrik mukozadaki kimyasal değişiklikler(61) kolonizasyonu kolaylaştırabilir (62). Kimyasal değişiklikler sonrası mukus hücrelerinin apikal membranına adheze olan HP ultrastrüktürel değişiklikler yapar.…”
Section: Kontrol Grubuunclassified
“…First, gastric acidity begins to diminish after decades of carriage of H. pylori and the gradual agerelated development of atrophic gastritis (15,31). Therefore, the H. pylori-positive stomach produces a lower acid load and less damage to the distal esophagus when reflux arises.…”
mentioning
confidence: 99%